2012
DOI: 10.1016/j.repc.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight/obesity and its association with sedentary behavior in children

Abstract: Objective: The aim of this study was to determine the prevalence of overweight and obesity in children in the northeast region of Portugal, and to examine its association with sedentary behavior. Methods: Data were collected on 1786 children (907 boys, 879 girls) aged 6 to 13 years. Body mass index was calculated from measured height and weight (weight in kg/height in m squared). Overweight and obesity were determined using the International Obesity Task Force cutoff values. Sedentary behavior was assessed bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
(1 reference statement)
2
12
0
2
Order By: Relevance
“…Previous research [ 45 ] indicates that sedentary behaviour has not been studied in the African culture. This study concurs with research from Western countries which indicate a high prevalence of sedentary behaviour among adolescents in todays society [ 46 , 47 ]. The present study found that sedentary behaviour among Ghanaian young people was mainly associated with screen use, especially computers, followed by television and videogames.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research [ 45 ] indicates that sedentary behaviour has not been studied in the African culture. This study concurs with research from Western countries which indicate a high prevalence of sedentary behaviour among adolescents in todays society [ 46 , 47 ]. The present study found that sedentary behaviour among Ghanaian young people was mainly associated with screen use, especially computers, followed by television and videogames.…”
Section: Discussionsupporting
confidence: 92%
“…A high prevalence of overweight and obesity (≈46%) was found among Portuguese children in this study which is not in complete agreement with previous studies. For example, Vasques et al (2012) found a prevalence of about 30% in children and adolescents aged 6 to 13 years using the IOTF cut points [ 47 ]. Sardinha et al (2011) studied Portuguese youth aged 10 to 18 years, and reported the prevalence of overweight and obesity contrasting two cut points 22.7% and 31.7% using the IOTF and WHO references, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In Iranian adolescents, the time spent on TV viewing was associated with an increased risk of obesity while obesogenic foods and physical activity had no effect on the frequency of obesity 19 . In Portugal, only 12.2% of children spend 1.5 hours or less on TV and computer and boys who spend less time on TV and computer were 75.4% less likely to be overweight/obese than those who spend more time 20 . Indicators of sedentary lifestyle, such as screen time and presence of a TV in the child's bedroom, were associated with overweight and obesity in Norwegian schoolchildren 21 .…”
Section: Discussionmentioning
confidence: 99%